2014
DOI: 10.1186/2193-1801-3-191
|View full text |Cite
|
Sign up to set email alerts
|

Carotid blood flow, cardiovascular and endocrine responses during head-up tilt in patients with acute cerebrovascular diseases

Abstract: The purpose of this study was to define common carotid blood flow (CBF), cardiovascular and endocrine responses during head-up tilt (HUT) in patients with acute cerebrovascular diseases (CVD). In 31 male patients with acute CVD (damage of the supratentorial area) and 21 age-matched control male subjects, we measured CBF, mean blood pressure (MBP), heart rate, stroke volume and cardiac output responses before (baseline), during and after HUT. We also measured plasma levels of antidiuretic hormone, adrenaline, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Additionally, It has also been shown that there was a significant decrease in the blood flow within carotid circulation in stroke patients when placed in the heads-up position. 20,21 This strengthens the argument that the utility of the heads-up CPR technique should be on a case-to-case basis and not "one size fits all." Thus, patients needing to be transferred, namely, cases that are taken from high-rise buildings, need to be considered separately because heads-up CPR may have possible adverse effects.…”
Section: Heads-up Cpr Experimental Modelssupporting
confidence: 57%
See 3 more Smart Citations
“…Additionally, It has also been shown that there was a significant decrease in the blood flow within carotid circulation in stroke patients when placed in the heads-up position. 20,21 This strengthens the argument that the utility of the heads-up CPR technique should be on a case-to-case basis and not "one size fits all." Thus, patients needing to be transferred, namely, cases that are taken from high-rise buildings, need to be considered separately because heads-up CPR may have possible adverse effects.…”
Section: Heads-up Cpr Experimental Modelssupporting
confidence: 57%
“…When CPR was used in combination with the transfer sheet (supine), it provided a higher mean depth of compression than the 45° and 90° stretchers. Furthermore, the percentage of depth‐enough reduction was higher in the transfer sheet patients than in the 45° stretcher group 20,21 …”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although the mechanism of the abnormal cerebral blood flow reduction in ME/CFS patients is not fully understood, one of the hypothesized mechanisms is that the abnormal cerebral blood flow reduction is related to an abnormal cardiac output reduction due to increased venous pooling and lack of venous return during the tilt test ( Timmers et al, 2002 , van Campen and Visser, 2018a ). It has previously been shown in healthy controls that cardiac output returns to normal pre-tilt test values within 1 min of the supine recovery phase ( Barde and Deepak, 2012 , Miyake et al, 2014 , Toska and Walløe, 2002 ). In ME/CFS patients the cardiac output in the post-test supine recovery phase has not been studied previously.…”
Section: Introductionmentioning
confidence: 97%